The Safety of Diagnostic Ultrasound in Ophthalmology - T. N. Kiseleva; M. S. Zaitsev; K. V. Lugovkina (Oftalʹmologiâ)
The literature review presents information about ultrasound use in diagnosis, therapeutic and surgical treatment of eye diseases. Due to experimental studies it was proved that ultrasound of different power, intensity and exposure causes thermal, mechanical and biological effect on the eye tissue. Thermal effect caused by ultrasonic energy absorption by biological tissues, which is converted from acoustic energy into thermal energy. The mechanical effect is determined by the amplitude of ultrasonic pressure acting on the eye structures during the examination. For the safety of ultrasound scanning, such concepts as thermal (TI) and mechanical (MI) indices have been introduced, which allows to control the level of acoustic impact on tissues. Ultrasound diagnosis in ophthalmology went a long way from one-dimensional echography (A-mode) to the complex scanning in real time, which allows to visualize different structural elements of the eye. Ultrasound eye examination is non-invasive and highly informative and thereby one of the main instrumental diagnosis methods in ophthalmology. Combination of images in gray scale, highly sensitive color and energy Doppler, 3D and sonoelastography to date greatly increased the diagnostic capabilities of ultrasound for simultaneous qualitative and quantitative assessment the eye and orbit in normal and pathological conditions. Therefore general ultrasonic diagnostic systems are widely used in clinical practice, with obligatory correction of TI and MI values. Recommendations of the international professional organizations such as Food and Drug Adminisration (FDA) and American Institute of Ultrasound in Medicine (AIUM))are widely used for the ultrasonic examination of eye pathology, according to which the lowest levels of exposure and intensity of the output acoustic signal (TI and MI) should be set to get a high-quality image. There are still a lot of clinical and experimental studies to determine the optimal modes of ultrasound eye and orbit examination. However, the safety of ultrasound and its effect on eye structures are still need to be studied.